Faktor-Faktor Yang Mempengaruhi Persebaran Pemanfaatan Ruko di Kota Malang - JAMIL, Achmad Maulana Malik ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development in urban areas is increasingly growing, especially inCentral Business Districtto meet the needs of the public for activity organization due to high economic growth. The urban planning must race with the physical development of the buildings as well as another urban infrastructure. The planning of trading centers must be adapted based on the existing various considerations. It isalso applicable in Malang City as well. The behavior and characteristics of the trading in Malang City is including the land use development of the trading in the form of shophouses. The phenomenon occurring lately is the abandonment of the land usewhich is sole in nature. The current land use tends to be pluralistic, integrated, and large-scaled (for example the superblock concept). The pluralistic land use is also a form of agglomeration of the trading facilitation. This can be seen in the provision of trading facilities in the form of shops lining in the trading district. The shift of the utilization of the shophouses’ function in Malang City, which initially was used for shophouses on its utilization was divided into, shopoffice- warehouse and shophouses.By the growing development and the varied utilization of shophouses in Malang, it could be formulated into a formulation of the problem which became the basic research study i.e. how did the factors affecton the utilization of shophouses in Malang City? And, how was the distribution pattern of the shophouses in Malang City? This research used descriptive quantitative method with a deductive approach, the total sample was 117 shops by using crosstabs and chi square analyses. The factors holding significant effect in the shop-houses utilization were the proximity to Central Business District, the proximity to settlements andthe proximity to markets. In addition, the utilization of shophouses which was in the form of offices and stores was significantlyaffected by the proximity to the office and proximity to the market, while for other utilization, it tended to be random. The recommendation of this research is that it needs to be studied further both by the point of view of the developers and the users in term of the utilization of shophouses to avoid the changes in their function. Therefore, the establishment of the growth agglomeration will stimulate the surrounding growths.